Celiac disease, eosinophilic esophagitis and gastroesophageal reflux disease, an adult population-based study. (July 2013) - Ludvigsson, Jonas F.; Aro, Pertti; Walker, Marjorie M.; Vieth, Michael; Agréus, Lars; Talley, Nicholas J.; Murray, Joseph A.; Ronkainen, Jukka
Abstract Objective. Celiac disease (CD) has been linked to gastroesophageal reflux disease (GORD) and eosinophilic esophagitis (EoE), but population-based studies of the prevalence of CD in these conditions are lacking, that is, the aim of this study. Materials and methods. An endoscopic study was carried out in 1000 randomly selected adults from the general population. CD was defined on the basis of positive serology in parallel with mucosal abnormalities of the small intestine. Any eosinophil infiltration of the esophageal epithelium was defined as esophageal eosinophilia and EoE was defined as having at least 15 eosinophils/high-power field in biopsies from the distal esophagus. We used Fisher's exact test to compare the prevalence of GORD, esophageal eosinophilia, and EoE in subjects with CD versus controls. Results. Four hundred subjects (40%) had gastroesophageal reflux symptoms (GORS), 155 (15.5%) had erosive esophagitis, 16 (1.6%) had Barrett's esophagus, 48 (4.8%) had esophageal eosinophilia, and 11 (1.1%) had EoE. CD was diagnosed in 8/400 (2.0%) individuals with GORS (vs. controls: 10/600 (1.7%), p = 0.81), in 3/155 (1.9%) with erosive esophagitis (vs. 15/845 controls (1.8%), p = 0.75), and in 2/48 (4.2%) individuals with esophageal eosinophilia (controls: 16/952 (1.7%), p = 0.21), but in none of those 16 with Barrett's esophagus (vs. 18/984 controls (1.8%), p = 1.0) or of the 11 individuals with EoE (controls: 18/989 (1.8%), p = 1.0). Conclusions. This population-based study found no increased risk of CD among individuals with GORD, esophageal eosinophilia, or EoE. CD screening of individuals with GORD or EoE of individuals with CD cannot be recommended.